2019
DOI: 10.1111/and.13321
|View full text |Cite
|
Sign up to set email alerts
|

Oxidised low‐density lipoprotein, a possible distinguishing lipid profile biomolecule between prostate cancer and benign prostatic hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) and prostate cancer (PCa) share common conditions such as lower urinary tract symptoms (LUTS) and dyslipidaemia. Whether an extensive lipid profile analysis could discriminate between BPH and PCa was the objective. Thirty‐six (36) BPH and twenty (20) PCa outpatients of a urology clinic plus forty (40) controls without LUTS, but normal PSA, were recruited. Body mass index (BMI), lipid profile (total cholesterol [CHOL], triglycerides [TG], high‐density lipoprotein [HDL], very‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…However, there was no signi cant association between obesity and prostate cancer. A similar nding by Asare and colleagues [31] in Ghanaian men attending Urology Clinic also found no signi cant association between obesity assessed by BMI and prostate cancer. Furthermore, a Nigerian prostate cancer detection study also found no signi cant association of obesity and prostate cancer [32].…”
Section: Resultssupporting
confidence: 51%
“…However, there was no signi cant association between obesity and prostate cancer. A similar nding by Asare and colleagues [31] in Ghanaian men attending Urology Clinic also found no signi cant association between obesity assessed by BMI and prostate cancer. Furthermore, a Nigerian prostate cancer detection study also found no signi cant association of obesity and prostate cancer [32].…”
Section: Resultssupporting
confidence: 51%
“…Besides, the Van et al study analyzed the relationship between lipid parameters and the pathological results of PCa and found that low Apo A-I and HDL were statistically significantly associated with PCa ( 10 ). The Asare et al study showed that LDL was significantly higher in a PCa group than a BPH group and had a strong positive association with the pathological results ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results are conflicting. Many studies have shown that cholesterol and LDL are significantly higher in PC and men with hypercholesterolemia are usually at higher risk of developing high-grade PC [ 72 , 73 , 74 ]. Moreover, one study suggests that extensive blood lipid profile could distinguish PC from BHP [ 73 ].…”
Section: Cholesterol Profile In Bloodmentioning
confidence: 99%
“…Many studies have shown that cholesterol and LDL are significantly higher in PC and men with hypercholesterolemia are usually at higher risk of developing high-grade PC [ 72 , 73 , 74 ]. Moreover, one study suggests that extensive blood lipid profile could distinguish PC from BHP [ 73 ]. Some studies did not find a connection between LDL and overall PC risk but did find association of high HDL and increased risk of high-grade PC [ 75 ].…”
Section: Cholesterol Profile In Bloodmentioning
confidence: 99%